(3GdTGeds - (3CejQ cGJH Hf CejQ YeQ Hf CejQ ZGRj GdaGQGHqj GdEJbGfj GdYejOj GdMfaj, CHh MfajI, bhGe GdOjf, J (B758 (3g`s; (3GdHROhj , Ydj Hf eMeO Hf GdMSjf Hf YHO GdcQje, aNQ GdGSdGe CHh GdMSf,J (B482 (3g` s
(3ChdgG (B:s
(3HGH eYQaI CMcGe GdYehe hGdeTJQc hGdeDhd s
(3BNQgG (B:s
(3bhdg (B" (3dCf GdTQW hbhY GdQchY bQHI , hgh de jTQY bQHI ai ZjQ GdUdGI s
(3GdfSNI HgG MhGTs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B328 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B192s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B8 - (3U (B245 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B112s
Keywords: (3CUhd Gdabgs